Meaningful vs. hedonic consumption: The effects of elevation on online sharing and information searching behaviors. (December 2019) - Jang, Wonseok (Eric); Lee, Joon Sung; Kwak, Dae Hee; Ko, Yong Jae
Highlights: This study examined individuals' online sharing behavior. This study examined individuals' online information search behavior. Meaningful video was more likely to share by individuals than hedonic video. Meaningful video created more interest from individuals than hedonic video. Abstract: Sharing has become one of the most prevalent behaviors in the online environment as the rise of social media enables individuals to share content (e.g., videos and pictures) more easily with others on social networking sites. Sharing has been mainly investigated from a reciprocal standpoint (exchange-based sharing), and there has been a lack of effort to expand our knowledge of sharing from prosocial and morality perspectives. In this regard, based on the dual process theory and the dual model of entertainment media, the current study examines the role of elevation in determining individuals' online sharing and information searching behaviors. The results indicate that participants exhibited greater intentions to share a meaningful video online and search for more information about the actor compared with a hedonic video (Experiment 1), and this effect was further moderated by participants' moral identity (Experiment 2) and different mindsets associated with a prosocial action (beneficiary vs. benefactor; Experiment 3). Theoretical and practical implications are discussed related to online sharing and entertainment media literature.